SUPERCRITICAL CARBON DIOXIDE EXTRACTION OF ESSENTIAL OIL FROM LIGNIFIED AQUILARIA SINENSIS - GWEE , YONG LING (2018)
Aquilaria sinensis which is a highly valuable fragrant resinous wood possesses biological activities and pharmaceutical benefits. In this study, the essential oil from lignified ring and resin of Aquilaria sinensis were extracted using carbon dioxide under supercritical condition.